Renal volume assessed by magnetic resonance imaging volumetry correlates with renal function in living kidney donors pre‐ and postdonation: a retrospective cohort study. (15th April 2018) - Lange, Daniel; Helck, Andreas; Rominger, Axel; Crispin, Alexander; Meiser, Bruno; Werner, Jens; Fischereder, Michael; Stangl, Manfred; Habicht, Antje
Summary: Renal function of potential living kidney donors is routinely assessed with scintigraphy. Kidney anatomy is evaluated by imaging techniques such as magnetic resonance imaging (MRI). We evaluated if a MRI‐based renal volumetry is a good predictor of kidney function pre‐ and postdonation. We retrospectively analyzed the renal volume (RV) in a MRI of 100 living kidney donors. RV was correlated with the tubular excretion rate (TER) of MAG3‐scintigraphy, a measured creatinine clearance (CrCl), and the estimated glomerular filtration rate (eGFR) by Cockcroft‐Gault (CG), CKD‐EPI, and modification of diet in renal disease (MDRD) formula pre‐ and postdonation during a follow‐up of 3 years. RV correlated significantly with the TER (total: r = 0.6735, P < 0.0001). Correlation between RV and renal function was the highest for eGFR by CG ( r = 0.5595, P < 0.0001), in comparison with CrCl, MDRD‐GFR, and CKD‐EPI‐GFR predonation. RV significantly correlated with CG‐GFR postdonation and predicted CG‐GFR until 3 years after donation. MRI renal volumetry might be an alternative technique for the evaluation of split renal function and prediction of renal function postdonation in living kidney donors.